2016
DOI: 10.4137/cmed.s38201
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Effects of Growth Hormone in the Body: Is it Really the Hormone for Growth?

Abstract: In this review, we analyze the effects of growth hormone on a number of tissues and organs and its putative role in the longitudinal growth of an organism. We conclude that the hormone plays a very important role in maintaining the homogeneity of tissues and organs during the normal development of the human body or after an injury. Its effects on growth do not seem to take place during the fetal period or during the early infancy and are mediated by insulin-like growth factor I (IGF-I) during childhood and pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
165
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(181 citation statements)
references
References 371 publications
(478 reference statements)
2
165
0
9
Order By: Relevance
“…Moreover, in our study [9] we found that plasma levels of IGF-I were in low values in these SCI patients. As we recently reported [26], liver production of IGF-I is not fully dependent on GH, but it is well known that the administration of the hormone or its normal secretion induces the expression of IGF-I in liver and many other organs and tissues, including the brain. Therefore, an analysis of GH secretion in response to specific stimuli should be mandatory in tetraplegic patients and a treatment with the hormone should be scheduled if GH-deficiency exists.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in our study [9] we found that plasma levels of IGF-I were in low values in these SCI patients. As we recently reported [26], liver production of IGF-I is not fully dependent on GH, but it is well known that the administration of the hormone or its normal secretion induces the expression of IGF-I in liver and many other organs and tissues, including the brain. Therefore, an analysis of GH secretion in response to specific stimuli should be mandatory in tetraplegic patients and a treatment with the hormone should be scheduled if GH-deficiency exists.…”
Section: Discussionmentioning
confidence: 90%
“…Particularly, the hormone plays a significant role at the cognitive level [25][26][27][38][39][40][41][42][43][44], even in the case that no GH-deficiency exists. Moreover, GH is an inducer of endothelial production of the vasodilator NO and recovers endothelial dysfunction [6,37,45]. Therefore, this hormone might be of utility in the prevention of the cascade of deleterious effects subsequent to SAH but also to recover the arteries most likely damaged in the case of our patient.…”
Section: Discussionmentioning
confidence: 90%
“…GH plays a key role in neural development [34] and also exerts important neuroprotective and neuroregenerative effects [24,26,27,[34][35][36][37]. Particularly, the hormone plays a significant role at the cognitive level [25][26][27][38][39][40][41][42][43][44], even in the case that no GH-deficiency exists.…”
Section: Discussionmentioning
confidence: 99%
“…We treated him according to our protocols for children with cerebral palsy, both in terms of medication received (GH and MT) and neurorehabilitation [22,23]. GH was prescribed not only because of the low height of the patient and low plasma IGF-I values, a very common finding in children with cerebral palsy [24], but also for the known effects of the hormone on brain repair after a damage [25][26][27][28], particularly on cognition, executive functions and working memory [27,[29][30][31][32]. These GH effects were also observed in the patient, as the great improvement in the BDIST showed (14 months in 16 months of treatment), mainly in areas related to cognitive functions.…”
Section: Discussionmentioning
confidence: 99%